Multicenter evaluation of a new ultrasound-guided biopsy device: Improved ergonomics, sampling and rebiopsy rates. - Duchesne N; Parker SH; Lechner MC; Gittleman MA; Kusnick CA; Elvecrog EE; Kaske TI; Gizienski TA (Breast Journal)
The purpose of this study was to evaluate performance, ergonomics, and immediate rebiopsy rate of a new vacuum-assisted biopsy (VAB) device for ultrasound-guided breast biopsies. Between December 2002 and April 2003, 113 patients meeting study criteria were biopsied at four centers using the new 9 gauge VAB device. The device has a radiofrequency-tipped probe, 360 degrees vacuum, a circumferential cutter, and a coaxial cannula for multiple sampling. Patient and procedural data included breast composition, lesion characteristics, number of samples, procedure time, and complications. Quality of samples, lesion access, and ergonomic features were assessed qualitatively and compared with prior experience with other biopsy devices. Immediate rebiopsy rate included high-risk lesions requiring surgical excision (obligate rebiopsy) and lesions requiring rebiopsy due to discordance or insufficient samples yielding nondiagnostic material. Data were analyzed using the Wilcoxon signed-rank test. One hundred thirteen patients aged 20-83 years (mean 52) were successfully biopsied with dense/fibrous breast tissue in 60% and dense/fibrous lesions in 49%. Lesions measured 6-63 mm (mean 17); 97% were masses. Five circumferential specimens (range 2-19) were obtained in 6 minutes (range 2-20). Operators rated safety and comfort comparable with existing devices and rated sample quality, breast/lesion penetration, and positioning ease/accuracy superior (p < 0.01). Diagnoses included 37 cancers, 70 benign, and six high-risk lesions with one upgrade from atypical ductal hyperplasia to ductal carcinoma in situ at surgery. Excluding obligate excision in high-risk diagnoses, the immediate rebiopsy rate was 2%. No complications required intervention. The new VAB device provides diagnostic samples and reduces sampling error defined by immediate rebiopsy rate. Compared with other devices, it is more ergonomic to target and position for sampling, particularly in dense breast tissue or lesions.